Регіональне дослідження показників науки та освіти в Україні - Тоцька, Олеся Леонтіївна; Totska, Olesia Leontiivna (Вінницький фінансово-економічний університет, 2011)
Проведено кластерний аналіз регіонів України за показниками науки та освіти на основі даних за 2008 рік. Для автоматизації розрахунків використано програмний пакет StatSoft Statistica 8.0. Отримано три групи областей з різними рівнями розвитку науки та освіти. The cluster analysis of the regions of Ukraine on the basis of indicators of science and education has been carried out. For automation of calculations a programmatic package StatSoft Statistica 8.0 is used. Three clusters of regions with different equals of development of science and education is received.
Regional research of indexes of science and education in Ukraine
Keywords: наука; science; освіта; education; кластерний аналіз; cluster analysis; показники; indicators; кластери; clusters